Single-atom catalysis : a forthcoming revolution in chemistry - Pagliaro, Mario, 1969- (Elsevier, 2019)
Single-Atom Catalysis: A Forthcoming Revolution in Chemistry reviews the latest developments, including whether or not this technology can become a technically and economically viable choice and whether existing challenges can be overcome to encourage its uptake. Beginning with an introduction to single-atom catalysis and current developments in the field, the book then reviews its role in potentially disruptive technologies, with a particular focus on applications in synthetic organic chemistry, solar hydrogen technologies and low platinum/platinum-free fuel cells. Other sections cover the steps needed for single-atom catalysis to become an industrially viable technology and its future outlook. Based on the extensive experience of its award-winning author, this book provides an authoritative guide on this novel approach.